PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS VIDEO PADA MATA PELAJARAN SKI KELAS VII DI MTS TERPADU BERKAH - Hajizah Hajizah; Rabbiatul Alawiyah; Ahmad Aspiani; Abdul Azis (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this study was to develop interactive video-based learning multimedia on SKI subjects with the theme of the Condition of Medina Society before Islam and the Event of the Prophet Muhammad's Hijrah to Medina. The research method used is Research and Development (R&D) with the aim of creating interactive video-based multimedia for MTs Terpadu Berkah students and determining the quality of interactive multimedia based on assessments by media experts, material experts, and technical assessments. Based on the findings, media experts have an average feasibility value in the good category, while material experts have an average feasibility value in the good category. Small group trials have an average score of good and in the good category, and field trials have an average score in the good category. Thus, as a result, the creation of interactive video-based multimedia can provide students' enthusiasm for learning in the learning process.